The Modular-Rating System in Pedagogical Higher Educational Institutions as The Basis for The Individually Oriented Teaching of The Physics Teacher (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This article describes the importance of the modular-rating system in pedagogical higher education institutions as the basis for the individually oriented teaching of the physics teacher